Covariates of acute respiratory infection in children under-five the 2013 Philippine national demographic and health survey - Rodriguez, Maria Victoria C. (UP Los Baños Journal, 2018)
The study was conducted to determine the effects of selected socioeconomic, demographic and environmental contamination variables on the prevalence of acute respiratory infection (ARI) among Filipino children below five years old. It utilized data from the 2013 National Demographic and Health Survey (NDHS) where a total of 16, 155 women aged 15-49 were interviewed. Children who were born to these women from 2008 to 2013 and are still alive during the survey period were the study cases (7,012 children). Multivariate logistic regression using Statistical Packages for the Social Sciences version 17.0 (SPSS v. 17.0) was used to determine significant risk factors related to ARI. The overall prevalence of ARI in children under five was six percent. Results show that the odds of contracting ARI is almost twice for children who are 12 to 23 months old compared with those in the 48 to 59 months age group. Furthermore, the odds of getting sick is 1.5 times higher in the Visayas than in the regional differentials where the odds of contracting the illlness is 1.6 times higher in the Visayas than in the National Capital Region. It is also interesting to note that children whose mothers are currently working are more likely to have ARI and that children belonging to the poorest and middle wealth categories are 1.5 times more susceptible to ARI than those in the richest quintile. Lastly, wether or not the birth of the child was wanted by the mother also emerged as a significant variable with children who are unwanted being more likely to manifest the disease.